Ordbogseksterne henvisninger – fra belæg til funktioner - Leroyer, Patrick (Nordiske Studier i Leksikografi, 2006)
External References in Dictionaries – From Attestation to Functions. While there has been a lot of metalexicographical interest in the use of internal cross references in dictionaries, the use of references to texts and sources outside the dictionary has been largely ignored. The purpose of this article is threefold: Firstly to examine the general practice of external references in printed and Internet dictionaries; secondly to develop the necessary theoretical principles, and finally to establish a set of guidelines for best practice. It is argued that external references should always be made according to the planned dictionary functions in order to provide problem-solving dictionary solutions to specific user problems in either communication or knowledge related user situations. The proposition defended here is that the selected external references should follow the same functional orientation as the dictionary articles from which they are derived.